PANCASILA SEBAGAI LANDASAN ILMU - Jennifer (Lembaga Kajian Ilmu Sosial dan Politik (LKISPOL), 2025)
Pancasila, as the foundational philosophy of the Indonesian state, not only functions as a guide for national life but also serves as a basis for various fields of knowledge, including management. The values enshrined in Pancasila act as ethical and moral guidelines in organizational management and decision-making processes. This paper is written as a way to explore the application of Pancasila in the development of management science, as well as how the mastery of Pancasila's values can shape a work ethic based on integrity. In the context of management, Pancasila serves as a moral and ethical guide that directs organizational management, decision-making, and interpersonal relations within an organization. The principles of Pancasila, when applied, can help create a more harmonious, just, and respectful environment, which in turn strengthens the organization's competitiveness. For instance, the first principle, Belief in One God, encourages leaders to uphold high integrity and maintain moral values in every decision they make. The second principle, Just and Civilized Humanity, teaches the importance of respecting human dignity in all interactions and policies implemented within the organization. This paper aims to provide a deeper understanding of the application of Pancasila in the development of management science. Furthermore, mastering the values of Pancasila can help shape a strong and ethical work ethic, which is essential in fostering professionalism in the workplace. This work ethic, grounded in moral and ethical values, motivates individuals to perform their tasks with dedication, uphold honesty, responsibility, and fairness, and contribute positively to their organizations. Therefore, applying Pancasila in management not only enhances individual performance but also strengthens national values, benefiting the overall development of Indonesian society.